Molecular basis of hydroperoxide specificity in peroxiredoxins: the case of AhpE from Mycobacterium tuberculosis - Zeida Camacho, Ari Fernando (2015)
Peroxiredoxins (Prxs) constitute a ubiquitous family of Cys-dependent peroxidases that play essential roles in reducing hydrogen peroxide, peroxynitrite and organic hydroperoxides in almost all organisms. Members of the Prx subfamilies show differential oxidizing substrate specificities that await explanations at a molecular level. Among them, alkyl hydroperoxide reductases E (AhpE) is a novel subfamily comprising Mycobacterium tuberculosis AhpE and AhpE-like proteins expressed in some bacteria and archaea. We previously reported that MtAhpE reacts ~104 times faster with an arachidonic acid-derived hydroperoxide than with hydrogen peroxide, and suggested that this surprisingly high reactivity was related to the presence of a hydrophobic groove at the dimer interface evidenced in the crystallography structure of the enzyme. In this contribution we experimentally confirmed the existence of an exposed hydrophobic patch in MtAhpE. We found that fatty acid hydroperoxide reduction by the enzyme showed positive activation entropy that importantly contributed to catalysis. Computational dynamics indicated that interactions of fatty acid-derived hydroperoxides with the enzyme properly accommodated them inside the active site favoring the anchorage of the enzyme in a reactive conformation. The computed reaction free energy profile obtained via QM/MM simulations is consistent with a greater reactivity in comparison with hydrogen peroxide. This study represents new insights on the understanding of the molecular basis that determines oxidizing substrate selectivity in the Prx family, which has not been investigated at an atomic level so far.